2023
DOI: 10.3390/ijerph20021359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Playing Exergames on Quality of Life among Young Adults: A 12-Week Randomized Controlled Trial

Abstract: The purpose of this paper is to investigate whether playing exergames can enhance quality of life among young adults and it examines the potential moderators. Methods: A 12-week randomized controlled trial was conducted. Quality of life was measured using the short-form 36-item version (SF-36) scale. All the participants were between 20 and 24 years old in Taiwan. Participants in the intervention group (n = 55) were asked to play exergames for 12 weeks, three times a week and 30 minutes at a time, while partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Physical gamified practice favors sociability or socialization processes. In fact, studies such as those by the authors of [57][58][59]62,64,66,68] agree with the study described by the author of [73], who found better social functioning and good mental health in young adults. The author of [66] expressed concern about the toxic behaviors that can gestate in social networks.…”
Section: Discussionsupporting
confidence: 79%
“…Physical gamified practice favors sociability or socialization processes. In fact, studies such as those by the authors of [57][58][59]62,64,66,68] agree with the study described by the author of [73], who found better social functioning and good mental health in young adults. The author of [66] expressed concern about the toxic behaviors that can gestate in social networks.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, physical function, role limitation due to physical health, general health, and vitality were significantly improved in the health-related quality of life evaluation. In a previous study of the exergame program for the older adults, among the SF-36 items, there were significant differences only in physical function, role limitation by physical health, social role functioning, and general health perceptions items [ 71 , 72 ]. As the home-based exergame program in this study consisted of exercises that directly affect physical function, significant improvements were seen in items related to physical function as well.…”
Section: Discussionmentioning
confidence: 99%